Keeping Up with the Joneses and the Welfare Effects of Monetary Policy - Juha Tervala (Aboa Centre for Economics (ACE), 2011)
This paper examines the implications of "keeping up with the Joneses" preferences (jealousy) for the welfare effects of monetary policy. I develop a New Keynesian model, where households are jealous and the central bank follows the Taylor rule. I show that the welfare effects of monetary policy over time depend significantly on the relative strength of the consumption externality caused by jealousy and the monopolistic distortion. If jealousy (the monopolistic distortion) dominates, then a decrease in the interest rate reduces (increases) welfare in the short run, but increases (reduces) welfare in the medium run.
Keywords: E40; E50; E52; 330; Monetary policy; jealousy; consumption externality